PROBLEMATIKA PENERAPAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PEMBATASAN USIA PERNIKAHAN: STUDI KASUS PERNIKAHAN ANAK DI KUA KECAMATAN TAMANAN - M. Sayyid Aqil Khoirul Anam; Hasbi Ash Shiddiqi (Universitas Nurul Jadid, 2025)
The phenomenon of child marriage continues to occur frequently despite Law Number 16 of 2019, which sets the minimum age for marriage at 19 for both men and women. This study aims to identify the factors contributing to the persistence of child marriage and to analyze the problematic implementation of this law at the KUA (Office of Religious Affairs) in Tamanan District , Bondowoso Regency. This study used a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation with the Head of the KUA, religious instructors, and P3N officers in each village. Data analysis was conducted using field techniques. research to find patterns and themes from the interview results. The results show that child marriage in the Tamanan District Office of Religious Affairs (KUA) is still caused by economic factors, culture, low education, premarital pregnancy, and the practice of engagement at school age. In its implementation, Law Number 16 of 2019 has been running quite well, but is still faced with low public legal awareness and the influence of permissive religious leaders. The Tamanan KUA has attempted to address this through socialization, marriage guidance ( Bimwin ), and collaboration with the village. This study concludes that the problems The implementation of the law is highly dependent on synergy between the government, religious leaders, and the community. It is hoped that the results of this study can be used as a reference by religious institutions and the government in strengthening outreach and oversight of the implementation of the marriage age restriction.